The challenges to fighting cyber-crime in Greater Accra Region of Ghana. - Akpesey, William Kofi Apkalu (KNUST, 2025)
A Thesis Submitted In Partial Fulfilment Of The Requirements For The Award Of The Degree Of Master Of Public Administration.